2011
DOI: 10.1007/s10278-011-9423-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RadLex Coverage and Term Co-occurrence in Radiology Reporting Templates

Abstract: Radiologists are critically interested in promoting best practices in medical imaging, and to that end, they are actively developing tools that will optimize terminology and reporting practices in radiology. The RadLex® vocabulary, developed by the Radiological Society of North America (RSNA), is intended to create a unifying source for the terminology that is used to describe medical imaging. The RSNA Reporting Initiative has developed a library of reporting templates to integrate reusable knowledge, or meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The results verify our findings in previous studies, which found an overall rate of 67%reporting elements derived from the RSNA reporting templates were matched to RadLex® terms (Hong et al, 2012), and suggest that the concepts that appear in the reporting templates occur frequently within free-text clinical reports and the reporting templates provide useful coverage of the "domain of discourse" in radiology reports .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results verify our findings in previous studies, which found an overall rate of 67%reporting elements derived from the RSNA reporting templates were matched to RadLex® terms (Hong et al, 2012), and suggest that the concepts that appear in the reporting templates occur frequently within free-text clinical reports and the reporting templates provide useful coverage of the "domain of discourse" in radiology reports .…”
Section: Resultssupporting
confidence: 88%
“…The elements of the reporting templates have been mapped to corresponding terms in standardized biomedical ontologies such as the RadLex® radiology lexicon and the Systematized Nomenclature of Medicine Clinical Terms (SNOMED CT®) by employing a semi-automated mapping tool called RadMap (Hong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…With the RDF, the knowledge pertaining to medical image interpretation can be stored as a set of triples, where each element of the triple can be referenced by an explicit uniform resource identifier (URI) to which resources can be linked. By linking to welldefined medical terminologies, such as RadLex [12][13][14], Foundational Model of Anatomy (FMA) [15], and SNOMED CT [16,17], an RDF-based approach can explicitly refer to a formalized set of concepts. With query languages that make use of triple-based patterns, such as the Simple Protocol and RDF Query Language (SPARQL), it is possible to create detailed queries for specific information.…”
Section: Introductionmentioning
confidence: 99%
“…Each reporting template has associated metadata, including information about the template's title, creator, subject, description, and date. The elements of the reporting templates have been mapped to corresponding terms in standardized biomedical ontologies such as the RadLex® radiology lexicon and the Systematized Nomenclature of Medicine Clinical Terms (SNOMED CT®) vocabulary [9].…”
Section: Introductionmentioning
confidence: 99%
“…Standardized terminologies are used to reduce ambiguity and improve the clarity of radiology reports and image annotations, and provide a uniform means of indexing radiological materials in a variety of settings [9]. In this study, we sought to evaluate how well the RSNA reporting templates covered the "domain of discourse" of actual radiology reports.…”
Section: Introductionmentioning
confidence: 99%